Medial Tibial Stress Syndrome Induced by Methotrexate: A Case Report - Maarten MOEN,; Adam WEIR,; Andre van RIJTHOVEN,; Guus REURINK,; Johannes Leonardus TOL,; Frank BACKX1, (Archives of Rheumatology, 2011)
Normally, the cause of medial tibial stress syndrome is the overloading of the tibia as seen frequently in athletes and military recruits. This case report describes a physically inactive 49-year-old male patient suffering from psoriatic arthritis with the classic symptoms associated with medial tibial stress syndrome. The symptoms were due to the use of methotrexate and ceased by lowering the dosage.